Mysterious and fascinating: DNA polymerase ɩ remains enigmatic 20 years after its discovery - Vaisman, Alexandra (DNA Repair (Amst), 2020)
With the publication of the first paper describing the biochemical properties of DNA polymerase iota (polι), the question immediately arose as to why cells harbor such a low-fidelity enzyme which often violates the Watson-Crick base pairing rules? Yet 20 years after its discovery, the cellular function of polι remains unknown. Here, we provide a graphical review of the unique biochemical properties of polι and speculate about the cellular pathways in which enigmatic polι may participate.